URGENSI PEMILIHAN KEPALA OTORITA MELALUI DEMOKRASI PERWAKILAN DENGAN SISTEM PENUNJUKAN LANGSUNG - Mentari, Mahardika Dewi (Jurnal Yuridis, 2024)
The Nusantara Capital City (IKN) is a designated region as the Capital of Indonesia, replacing the DKI Jakarta. As a special administrative region, IKN led by a Chief Authority, whose appointment is directly designated, appointed, and terminated by the President in consultation with the DPR. This article delves deeply into the democratic phrase within the provisions of Article 18 paragraph (4) of the UUD 1945. The importance of electing the Chief Authority through direct appointment, and the participation of the people in the election of the Chief Authority. This research is a normative empirical legal study, utilizing a legislative framework approach and a survey involving 20 respondents, based on qualitative analysis. The results of this research indicate that the democratic phrase in Article 18 paragraph (4) of the 1945 Constitution is not accommodated in the IKN Law. The urgency of direct appointment in elections is to streamline bureaucratic processes, resulting in a greater role for the central government, Furthermore, the absence of a Regional Budget (APBD) for conducting regional elections, and from the distributed questionnaires, it is evident that, on the whole, people are aware of the plan to relocate the capital city but are unaware of who the local leaders are and how the selection process for the Chief and Deputy Chief Authority is conducted